2017
DOI: 10.21307/acee-2017-027
|View full text |Cite
|
Sign up to set email alerts
|

Estimation Of The Seasonal Demand For Cooling Based On The Short-Term Data

Abstract: In accordance with the requirements of the Directive on the energy performance of buildings [1], the energy performance of a building based on measurements may be an alternative for a computational one. In practice, it is important that the method should be relatively simple, based on short-term measurements in the real object. The annual heat consumption for heating and ventilation in reference climatic conditions is the basic component of the energy performance of buildings. The annual energy consumption for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…determination of seasonal energy demand for cooling based on short measurements was also shown [38]. On-site measurements of energy consumption for heating and DHW installations were presented in [39,40].…”
Section: Study Sidementioning
confidence: 99%
See 1 more Smart Citation
“…determination of seasonal energy demand for cooling based on short measurements was also shown [38]. On-site measurements of energy consumption for heating and DHW installations were presented in [39,40].…”
Section: Study Sidementioning
confidence: 99%
“…On-site diagnostics of mechanical ventilation systems and of cooling sources for air conditioning systems in office buildings were also presented in [36,37]. The determination of seasonal energy demand for cooling based on short measurements was also shown [38]. On-site measurements of energy consumption for heating and DHW installations were presented in [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…H-m method is based on linear regression between H-which is the ratio of the average power delivered to the building in a given day to the difference of internal and external temperature, and the value of m which is a "meteorological" variable defined as the ratio of the solar irradiance to the difference of internal and external temperature, according to EN 15603:2008). In the paper [13] the possibility of using the H-m method in the office building was analyzed. It has been shown that the determination of energy consumption for cooling in the cooling season is possible only based on the cooling power measurements in the building in the entire cooling season.…”
Section: Building Energy Performance Certificates Based On Measurementsmentioning
confidence: 99%
“…As a result, there has been a need for on-site diagnostics of air conditioning installations, which should include energy efficiency assessments whether it meet the requirements of the building. [4,7,8] and in the current paper, • the on-site the diagnostics of indoor environment quality, the results are presented in [4,9], • the measurement based drawing up of energy performance certificates, the results are presented in [4,[10][11][12][13]. Full diagnostics is understood as a combination of inspection and diagnostic measurements.…”
Section: S T R E S Z C Z E N I Ementioning
confidence: 99%
“…Results of the cooling source diagnostics were used to determine the energy performance of a building based on measurements [13].…”
Section: S T R E S Z C Z E N I Ementioning
confidence: 99%